2018
DOI: 10.1177/0022034518768536
|View full text |Cite
|
Sign up to set email alerts
|

Racial Inequalities in Oral Health

Abstract: Together with other social categories, race has been at the core of much scholarly work in the area of humanities and social sciences, as well as a host of applied disciplines. In dentistry, debates have ranged from the use of race as a criterion for the recommendation of specific dental procedures to a means of assessing inequalities in a variety of outcomes. What is missing in these previous discussions, though, is a broader understanding of race that transcends relations with genetic makeup and other indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(127 citation statements)
references
References 52 publications
4
114
0
9
Order By: Relevance
“…[69][70][71] In a review of seven studies, Slade found the prevalence of dental pain ranged from 5-33% and to increased with child age, caries severity, and decreasing socio-economic status. People from LMIC and indigenous populations in high income countries, have a lifetime history of dental pain that generally exceeded 50% of children [72][73][74][75][76][77] Dental problems can result in lost time from school and to negatively impact on school performance possibly exacerbating social inequalities. 4,[78][79][80][81][82][83][84] Numerous studies show that untreated dental caries and associated oral problems substantially decrease quality of life for both the child, as well as their caregivers.…”
Section: Childrenmentioning
confidence: 99%
“…[69][70][71] In a review of seven studies, Slade found the prevalence of dental pain ranged from 5-33% and to increased with child age, caries severity, and decreasing socio-economic status. People from LMIC and indigenous populations in high income countries, have a lifetime history of dental pain that generally exceeded 50% of children [72][73][74][75][76][77] Dental problems can result in lost time from school and to negatively impact on school performance possibly exacerbating social inequalities. 4,[78][79][80][81][82][83][84] Numerous studies show that untreated dental caries and associated oral problems substantially decrease quality of life for both the child, as well as their caregivers.…”
Section: Childrenmentioning
confidence: 99%
“…The institutional racism contributing to much of the participants’ reluctance to attend for dental care requires a whole of society shift [ 23 ]. Certainly, the recent Black Lives Matter movement has raised awareness of this, as has the increased profile of many prominent Indigenous Australian leaders.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the recent Black Lives Matter movement has raised awareness of this, as has the increased profile of many prominent Indigenous Australian leaders. The role of racism in oral health inequalities has been documented at a global level [ 23 ]. Although there is limited evidence of successful initiatives to address this, there are some encouraging results from the general health arena in this space [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature review from field experts has come to similar conclusions: “racial health inequalities should be of primary concern for both policy makers and researchers” . However, the authors caution that much of the inequality can be attributed to the overrepresentation of racial minorities in lower income groups …”
Section: Discussionmentioning
confidence: 91%